The religion-chivalrous vision of Ukraine in «The Testament» by Taras Shevchenko – «The Diptych» by Valentyn Sylvestrov - Драганчук, Вікторія Миколаївна; Drahanchuk, Viktoriia M. (Rivne State University of the Humanities, 2015)
The concept of Shevchenko’s vision of Ukraine, called the «religious and chivalrous», based on the national mental basis, is proposed. «The Diptych» by V. Sylvestrov, what is entered in a musical prayer space, is interpreted as «two testaments»: divine and human. The first part is written on the Gospel text of the prayer «Our Father» («Pater Noster»). The second part is written by the Shevchenko’s poem. Valentyn Sylvestrov is a composer, which uniquely provides an opportunity to delve deeper into Shevchenko’s poetry. The composer believes that Shevchenko-Kobzar is a «singer of Psalms» and from this position comes to understanding of the poet’s texts in the musical interpretation. When Shevchenko created a mystical «The Testament» he became a Christian poet-mystic. The composer treats the idea of «The Testament» for people extremely thin and spiritually. He contains a singing in the context of «high treble» in a literal and figurative spiritual sense. The theme does not sound in the bass or baritone that could symbolize Cossack Poet’s voice. «The Testament» voiced «divine» soprano sotto voce, the symbol a «heavenly», «high-frequency» music. In the first movement the themes motion reminiscent a well-known Hordii Hladkyy’s melody. The next development is enlightened and meditative. It is alleged that the composer is realizes the Kobzar’s idea in the aspects of cardiocentrism and spiritual will-desire. The meaning of «The Testament» is clearing Ukraine of a common sin. So we see prayer-religious sense of Sylvestrov’s musical interpretation.
Keywords: spiritual-chivalrous vision of Ukraine; hymns; musical interpretation; musical space; choral sound